The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/sports9070094
|View full text |Cite
|
Sign up to set email alerts
|

The Training Characteristics of Recreational-Level Triathletes: Influence on Fatigue and Health

Abstract: Little is known about how recreational triathletes prepare for an Olympic distance event. The aim of this study was to identify the training characteristics of recreational-level triathletes within the competition period and assess how their preparation for a triathlon influences their health and their levels of fatigue. During the 6 weeks prior to, and the 2 weeks after, an Olympic distance triathlon, nine recreational athletes (five males, four females) completed a daily training log. Participants answered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Exercise-induced fatigue is a common phenomenon during exercise, and its mechanisms mainly include peripheral and central mechanisms [9]. Central fatigue is a protective inhibition of the central nervous system; the purpose is to prevent excessive functional failure of the body [10]. It is known that central fatigue can be affected by many factors and there are significant individual differences, and the environment is one of the main factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-induced fatigue is a common phenomenon during exercise, and its mechanisms mainly include peripheral and central mechanisms [9]. Central fatigue is a protective inhibition of the central nervous system; the purpose is to prevent excessive functional failure of the body [10]. It is known that central fatigue can be affected by many factors and there are significant individual differences, and the environment is one of the main factors [11].…”
Section: Introductionmentioning
confidence: 99%
“…The latter had also been preparing for draft-legal OD competition. The OD triathlon personal best times of our males were, nonetheless, faster than those of the athletes who participated in Falk Neto et al’s prospective study of age-group-level OD training [ 16 ]. They were also faster (at 2:13:25 ± 0:16:07 vs. 2:12:24 ± 0:02:54; in hh:mm:ss) than Aoyagi et al’s (2021) nine younger “faster” well-trained males [ 6 ].…”
Section: Discussionmentioning
confidence: 93%
“…In no individual training block or individual triathlon discipline did the average proportion of swim, cycle and run training that the athletes spend in zone 1 exceed 56%. Falk Neto et al [16], whose intensity zones were set via RPE and guidelines in the literature and whose training data were prospective, reported that their slower age-group athletes spent 47% of training time in z1, 25% in z2 and 28% in z3. Vleck (2010) [14,35], using the same method of ascribing training intensity level as was used in this study, but over 30 weeks of prospective longitudinal data collection, reported that their 8 faster triathletes spent 70.4%, 6.1% and 9.1% of their overall training time in their intensity levels 1-2, 3 and 4-5, respectively, i.e., in z1, z2 and z3, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations